Instructional Competence and Faculty Performance among Maritime Schools in Central Luzon - Abad, Mirasol; Manalo, Kristine (Future Science / FSH-PH Publications, 2020)
The study investigated into the maritime faculty quality and excel-lence in education, mainly because they oversee facilitation of their students learning experiences. The effectiveness of their teaching is one of the factors that determine how well students' cadets would do in their voyage towards knowledge and acquisition. Thus, the advo-cacy to promote academic excellence and quality maritime education in the Philippines, as Philippine Merchant Marine Academy aims to be a center of maritime research making this institutional research in a regional scope to evaluate the instructional competence and faculty performance among maritime schools in Central Luzon. Descriptive survey design was used and this research was conducted in the ter-tiary level of the public and maritime schools in Region III. School year 2018-2019. The locale of the study is the three school duly rec-ognized by Commission on Higher Education (CHED). The respond-ents of the study were twenty-eight (28) technical maritime faculty from central Luzon offering a program of study of Bachelor of Science in marine transportation and in Bachelor of Science in marine engi-neering. Questionnaire was the main instrument used for the data collection. Pearson Moment Correlation, ANOVA, means, percentages and standard deviations were used to analyze the data. The results of the study showed that the quality of teachers was high in terms of their academic and professional qualifications, and it did reflect much in the performance of the students.